Fast profits: Investor sentiment and stock returns during Ramadan - Białkowski, Jędrzej; Etebari, Ahmad; Wisniewski, Tomasz Piotr (Journal of Banking & Finance, 2012)
Observed by more than 1.5 billion Muslims, Ramadan is one of the most celebrated religious traditions in the world. We investigate stock returns during Ramadan for 14 predominantly Muslim countries over the years 1989–2007. The results show that stock returns during Ramadan are significantly higher and less volatile than during the rest of the year. No discernible declines in market liquidity are recorded. We find these results consistent with a notion that Ramadan positively affects investor psychology, as it promotes feelings of solidarity and social identity among Muslims world-wide, leading to optimistic beliefs that extend to investment decisions.